Efficiency of the Public Sector Support Systems for Creating Innovative Milieu - Gyamfi, Solomon (Univerzita Pardubice, 2021)
The proponents of the innovative milieu concept contend that every support system should create supportive environment. The effects of public policy on R&D activities of the firm, impact of public funding such as subsidies and grants are the creation of the national innovation policy with entrenched public sector support systems. An efficient and successful public policy with support systems both financial and non-financial should meet the efficiency threshold to justify the need for increasing government expenditure in R&D. In lieu of the worsening public finance deficits, most current is the advent of the Covid-19 pandemic outbreak, which has wreaked havoc in the public expenditure and at the same time the pressing motive of concurrent need for innovation to sustain competitiveness of the economies in the world, public support systems should create innovative ecosystems that benefit all economic entities and society at large. However, due to market and government failures, the intended purpose of support is not achieved. Since the public sector play the role as the creator of the enabling environment for firms? innovation activities, support programs and policies should invoke collaborations, leading to firm innovation performance. The aim of the dissertation was in two folds, 1. to explore how SMEs innovative activity fuels the attraction of public support systems in the creation of an innovative environment for SMEs innovation, and 2. to measure how efficient the financial and nonfinancial public support systems and framework conditions facilitate the innovation performance of SMEs in the European Union countries.
Keywords: systémy podpory; inovace; spolupráce; sociální kapitál; lidský kapitál; support systems; innovation; collaboration; social capital; human capital